Beyond Halal Cuisine: A Comprehensive Exploration of Shariah Compliance in Tourism and Hospitality - Rosli, Nur Liana; Jamaludin, Mohamad Aizat Bin; Ahmad, Anis Najiha Binti (Tazkia Islamic Finance and Business Review, 2024)
This study aims to comprehensively explore Shariah compliance in tourism, extending beyond halal cuisine, to encompass prayer facilities, gender segregation, modesty restrictions, and ethical considerations. Utilizing a combination of extensive literature review, case studies, and expert opinions, this research offers a comprehensive analysis of various aspects of Shariah compliance in tourism, providing a holistic understanding of its implications. The research identifies significant factors influencing Shariah compliance in tourism, including the availability of prayer facilities, adherence to gender segregation norms, enforcement of modesty restrictions, and consideration of ethical principles. These findings underscore the multifaceted nature of Shariah compliance in hospitality firms and destinations, highlighting the importance of addressing diverse requirements to cater to Muslim travelers effectively. The insights gleaned from this research can inform hospitality firms and destinations about the importance of accommodating diverse Shariah requirements beyond halal food, thus enhancing the overall experience for Muslim travelers. Moreover, this study underscores the need for proactive measures to ensure Shariah compliance, which can contribute to the competitive advantage of tourism businesses in Muslim-majority markets. This research provides a comprehensive analysis of Shariah compliance in tourism, extending beyond halal cuisine to encompass various aspects such as prayer facilities, gender segregation, modesty restrictions, and ethical considerations, thereby filling a significant gap in existing literature.